Gene effects for pod characteristics in groundnut (Arachis hypogaea) - KUMAR, S SUDHEER; PATEL, S A (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during kharif 1995 to estimate the relative importance of additive, dominance and epistaticgene effects in the inheritance of pod characteristics in 4 groundnut (Arachis hypogaea L.) crosses at the University, Anand.Most of the pod and seed characters were governed by additive genetic effects in crosses between spanishbunch and virginia runner('Chico' X 'JSP 23' 'Chico' x 'GG 11'). In spanish bunch and virginia bunch cross ('Chico'X 'TMV 1O') pod length and pod width were governed by additive gene effects while 1O-pod weight, 1OO-kernel weight and shellingout-turn were governed by duplicate type of epistasis. In cross between 2 spanish bunch parents all the other traits barring 1O-pod weight and 100-kernel weight were governed by additive and x additive type of gene effects. In all the crosses except 'Chico' X 'TMV 10' selection for pod and seed characters can be practicedfollowing pedigree method of breeding